Mean platelet volume is decreased in HIV‐infected women. Issue 9 (5th June 2013) - Qadri, S; Holman, S; DeHovitz, J; Crystal, H; Minkoff, H; Lazar, JM
Abstract : Objectives: HIV infection is associated with higher than expected cardiovascular event rates and lowered platelet counts. These conditions are associated with an elevation of mean platelet volume (MPV). The present study compared MPV in HIV‐infected and uninfected women and identified factors influencing MPV values in HIV‐infected women. Methods: A total of 234 HIV‐infected and 134 HIV‐uninfected participants from the Women's Interagency HIV Study (WIHS) had MPV values obtained. HIV‐infected women were older, were more likely to have diabetes and had higher triglyceride levels than HIV‐uninfected women. Results: The mean platelet count was lower in HIV‐infected vs. uninfected women [249 cells/μL (95% confidence interval (CI) 238, 259 cells/μL) vs. 276 cells/μL (95% CI 265, 287 cells/μL), respectively; P < 0.01]. Adjusted mean MPV values were lower in the HIV‐infected than in the uninfected group [8.66 fL (95% CI 8.52, 8.79 fL) vs. 9.05 fL (95% CI 8.87, 9.24 fL), respectively]. In multiple regression analysis, after adjusting for other covariates, MPV was positively associated with platelet count, and negatively with HIV infection (model R 2 = 0.20; P < 0.01). In multiple regression analysis confined to HIV‐infected women, a lower MPV was independently associated with a history of AIDS‐defining illness ( R 2 = 0.28; P = 0.03), but not with nadir CD4 count or highly active antiretroviral therapy (HAART) use. Conclusions: HIV‐infected women had lower MPV values than uninfected women, suggesting impaired production rather than increased destruction. Higher than expected cardiovascular event rates cannot be attributed to greater platelet reactivity as measured by MPV.